2012
DOI: 10.1186/1756-3305-5-265
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasite infections in immigrant children in the city of Rome, related risk factors and possible impact on nutritional status

Abstract: BackgroundParasitic diseases can represent a social and economic problem among disadvantaged people - even in developed countries. Due to the limited data available concerning Europe, the aims of the present study were to evaluate the presence of parasites in immigrant children and the risk factors favouring the spread of parasites. Subsequently, the possible correlation between nutritional status and parasitic infections was also investigated.FindingsA convenience sample of two hundred and forty seven immigra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 15 publications
2
26
0
6
Order By: Relevance
“…10,11,18,32 Similar to previous studies, no relationship was found between having symptoms and the presence of imported infectious diseases, suggesting that screening protocols should be carried out regardless of clinical status. 9,33 The prevalence of pathogenic infectious disease was high (73%).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…10,11,18,32 Similar to previous studies, no relationship was found between having symptoms and the presence of imported infectious diseases, suggesting that screening protocols should be carried out regardless of clinical status. 9,33 The prevalence of pathogenic infectious disease was high (73%).…”
Section: Discussionsupporting
confidence: 66%
“…More than one-quarter of our study population presented coinfection by different imported infectious diseases, being similar to previous studies reporting from 9% to 35% of coinfection. 7,10,32 The presence of coinfection should always be considered since a delay in treatment may, in some cases, lead to serious consequences in both the short term (malaria) and the long term (HIV, TB, HBsAg, schistosomiasis, and strongyloidiasis) with respect to the health of the subject involved as well as the public health system. Furthermore, coinfection may alter the normal course of some infections, such as schistosomiasis and viral hepatitis, HIV and viral hepatitis, or HIV and strongyloidiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, with regard to asymptomatic parasitemia, little information exists that would establish a special relationship with nutrition and motor performance, especially in African children living in rural settings. Moreover, currently available information is inconsistent, and the relationship between parasitemia, nutrition, and motor performance remains unclear (Filho et al, ; Manganelli et al, ; Staat et al, ).…”
mentioning
confidence: 99%
“…However, nausea, diarrhea, abdominal pain, loss of body weight, and pruritis ani have also been reported during taeniasis. 16,24,25 [26][27][28][29] One important fi nding emerging from our comparison of children with E. vermicularis and T. saginata was the increase in appetite, which was more prevalent in the T. saginata group.…”
Section: Resultsmentioning
confidence: 99%